2007
DOI: 10.1103/physrevlett.99.164801
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of Electro-Optic Monitors for Femtosecond Electron Bunches

Abstract: The longitudinal profiles of ultrashort relativistic electron bunches at the soft x-ray free-electron laser FLASH have been investigated using two single-shot detection schemes: an electro-optic (EO) detector measuring the Coulomb field of the bunch and a radio-frequency structure transforming the charge distribution into a transverse streak. A comparison permits an absolute calibration of the EO technique. EO signals as short as 60 fs (rms) have been observed, which is a new record in the EO detection of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 13 publications
0
56
0
Order By: Relevance
“…Schematics for three of the most widely used detection schemes are contained in Berden et al [7]. All these schemes rely on polarization changes due to the Pockels effect to extract the bunch profile.…”
Section: A Current Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…Schematics for three of the most widely used detection schemes are contained in Berden et al [7]. All these schemes rely on polarization changes due to the Pockels effect to extract the bunch profile.…”
Section: A Current Techniquesmentioning
confidence: 99%
“…The next advancement in EOS was the development of a single shot technique that relies on spectral decoding [3,7,8,16]. Here instead of an ultrashort pulse, a stretched pulse is used as a probe and only the polarization state corresponding to the 1 " 10 axis is examined.…”
Section: A Current Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the Coulomb field of sub-ps electron bunch structures with some 100 pC charge can be measured with about 200 fs resolution by the spectral decoding technique [3,4]. Also, measuring the coherent transition radiation has proven to be a suitable method to analyze the temporal profiles of electron bunches [5]. A drawback of both methods is that they require a crystal or a metal foil close to or even in the path of the electrons and, thus, can either trigger wakefields or distort the electron bunches otherwise.…”
Section: Introductionmentioning
confidence: 99%